Formation of Religious Spiritual Character from the Perspective of Islamic Education Philosophy at SDIT Semarak - Rejabil Anbia; Putri Adelia; Eka Yanuarti (Indonesian Journal for Islamic Studies, 2024)
Education is a deliberate process that aims to maximize the potential of engaged learners by equipping them with the knowledge, abilities, and moral qualities that the nation and society demand, in addition to their religious beliefs and self-control. The research aims to identify the system of religious spiritual character formation from the perspective of Islamic educational philosophy at SDIT Semarak. This research is field research carried out by the author, using the Qualitative Descriptive Research method, namely describing clearly what happens in the field, which produces data in the form of written and verbal data from the behavior of people who can be observed. A qualitative approach with analytical techniques, namely content analysis, data reduction and data verification. The results of the research show that the formation of religious spiritual character at SDIT Semarak is realized through the daily habituation of students and the entire school community from morning until after school and there are also additional hours for extracurricular activities related to character values held in an integrative manner by all levels. school. It can be concluded that with daily habits that are integrated with spiritual character, SDIT Semarak students feel more helped in realizing religious spiritual character in themselves.